Estudio y desarrollo de la documentación requerida por la norma de gestión de calidad ISO 9001:2008 para la empresa SC Ingeniería SAS ubicada en la ciudad de Armenia Quindío. (2015)
This graduation project aims to study and document the processes of the company SC Ingeniería SAS taking into account the requirements of the NTC 9001: 2008 norm, for the development of this objective parameters are established in order to determine a qualitative research. SC Ingeniería is a company dedicated to perform routine maintenance, civil works, remodeling and equipment rental to Exito stores as a key part for their operation. In this work there is a division of three parts and the commitment and help from the staff as well as from the general manager is evidenced for its development, where in the first instance the current status of the company is evaluated through a checklist with the demanded requirements and a SWOT matrix. The second step corresponds to the amendment, defining and updating of the strategic platform of the company, which also includes the completion of the process map, where the strategic, missionary, support and evaluation processes are identified. During the development of the third step, the characterization of the established processes, documentation of procedures, implementation of the quality and development of work instructions manual, forms and records in accordance with the requirements under the NTC 9001: 2008 norm, thus facilitates the future implementation of the Quality Management System designed for the company. Finally, this project allows identifying the operational side of the company and providing a proper operational performance, in a more organized and satisfactoria way to both the company and for their potential customers.